Different action of a specific NR2B/NMDA antagonist Ro 25-6981 on cortical evoked potentials and epileptic afterdischarges in immature rats - Szczurowska, Ewa; Mareš, Pavel (Brain research bulletin, 2015)
Ro 25-6981 maleate is a highly selective and activity-dependent antagonist of NMDA ionotropic glutamate receptors containing NR2B subunit (NR2B/NMDARs). The aim of our study was to investigate the influence of Ro 25-6981 administration in developing rats on physiological (single and paired pulse cortical interhemispheric evoked potentials) and epileptic brain activity (cortical afterdischarges (ADs)). Electrophysiological experiments were performed in animals with epidurally implanted electrodes at postnatal days (P) P12, P18, and P25. The drug was injected intraperitoneally at a dose of 1 or 3mg/kg. Control animals were injected with saline (1ml/kg). Single interhemispheric responses were evoked with 0.5-ms biphasic pulses with intensities increasing from 0.4 to 5mA, paired-pulse responses were elicited by twofold threshold intensity. The ADs were elicited by series of 15-s of 1-ms pulses at 8-Hz frequency. Firstly, six stimulations with stable suprathreshold intensity repeated at 30-min intervals were used to determine the time course of Ro 25-6981 effects against ADs in P12 animals. Secondly, similar experiment was performed in all age groups of animals but with 20-min intervals as well as a further experiment using stimulations with stepwise intensities increasing at 10-min intervals from 0.2 to 15 mA. Pretreatment with the 3-mg/kg (but not the lower) dose of Ro 25-9681 decreased significantly the amplitude of single responses evoked with higher stimulation intensities in P12 and P18 animals. Both doses affected responses in P25 animals, only the 1-mg/kg dose was more efficacious than the 3-mg/kg one. Paired pulse responses were not affected by either dose of Ro 25-6981 in any age group. Ro 25-9681 clearly influenced the duration of ADs only in P12 animals. The 1-mg/kg dose did not change the duration of ADs whereas the 3-mg/kg dose suppressed progressive prolongation of ADs with repeated stimulations. This effect was seen even 110-min after the drug injection. The modification of ADs, i.e. stimulations with stepwise increasing intensities (10 min intervals) was used to demonstrate possible dependence on activity. The Ro 25-6981 was administered immediately after the 4-mA stimulation (i.e. when rats experienced six ADs on the average). The 3-mg/kg dose resulted in shorter ADs after high stimulation intensities in P12. There were no significant effects in older animals, only a tendency to ADs shortening was observed in P25 rats. In conclusion, our results indicate that Ro 25-6981 as a selective antagonist of NR2B/NMDARs exhibit age- and activation-dependent anticonvulsant action at early postnatal development. In contrast, the influence of Ro 25-6981 on physiological excitability induced by single pulse stimulation of sensorimotor cortex does not depend on age. This compound may thus represent a useful antiepileptic agent in immature brain since its action against ADs prolongation can be observed even 110 min after the single administration of the drug.
Keywords: receptory N-methyl-D-aspartátu; membránové potenciály; Phenols; záchvaty; Rats; senzorimotorický kortex; Sensorimotor Cortex; Cortical responses; NR2B subunit antagonist; antikonvulziva; Rats, Wistar; mužské pohlaví; Receptors, N-Methyl-D-Aspartate; Seizures; Membrane Potentials; fenoly; krysa rodu Rattus; věkové faktory; Rat; Piperidines; zvířata; Anticonvulsants; Cortical epileptic afterdischarges; elektrická stimulace; Age Factors; NMDA receptors; Postnatal development; potkani Wistar; piperidiny; Electric Stimulation; Male; Animals